Entropy Optimization of Third-Grade Nanofluid Slip Flow Embedded in a Porous Sheet With Zero Mass Flux and a Non-Fourier Heat Flux Model - Loganathan, K.; Muhiuddin, G.; Alanazi, A. M.; Alshammari, Fehaid S.; Alqurashi, Bader M.; Rajan, S. (Frontiers in Physics, 2020)
The prime objective of this article is to explore the entropy analysis of third-order nanofluid fluid slip flow caused by a stretchable sheet implanted in a porous plate along with thermal radiation, convective surface boundary, non-Fourier heat flux applications and nanoparticle concentration on zero mass flux conditions. The governing physical systems are modified into nonlinear ordinary systems with the aid of similarity variables and the outcomes are solved by homotopy analytic scheme. The impression of certain governing flow parameters on the nanoparticle concentration, temperature, velocity is illustrated through graphs, while the alteration of many valuable engineering parameters viz. the Nusselt number and Sherwood number are depicted in graphs. Entropy generation with various parameters is obtained and discussed in detail. The estimation of entropy generation using Bejan number find robust application in power engineering and aeronautical propulsion to forecast the smartness of entire system.